Using Video Annotation Software to Develop Student Self-Regulated Learning : Final Report. - Dawson, Shane; Pardo, Abelardo; Mirriahi, Negin; Gasevic, Dragan; Kingstone, Alan (Office for Learning and Teaching, 2016)
Teachers and students function in a world of paradox and pedagogical binaries: students must demonstrate dramatically more advanced 21st Century skills derived from educational environments that have fundamentally been unchanged since the mid 19th Century. However, the teaching and learning practices of the past provide little value in enabling our students to cope with the complexities of future career requirements. This is the final report from a project that sought to further research and develop a social annotation technology called the Collaborative Lecture Annotation System (CLAS). The tool was initially designed and developed by the project team to leverage the artefacts of traditional didactic modes of teaching for application into more social learning oriented models across all disciplines. The technology incorporates a suite of fine-grained learning analytics, to allow students to assess their learning progression, and to allow teachers to monitor the development of self-regulated learning skills and identify the need for learning support and guidance that is both automated and scalable.